Rare Earth Elements in Dinosaur Bones Across the Embryo-Adult Spectrum - Wang, Shuanglong; Huang, Timothy D.; Yan, Runhan; Chen, Huanwen; Zhang, Shitao; Li, Xiaobo; Kótai, László; Reisz, Robert R. (Frontiers in Earth Science, 2020)
There is broad consensus that many bones of extinct vertebrates contain Rare Earth Elements (REE) and other trace minerals that have been incorporated and enriched into the fossil during diagenesis. During fossilization, apatite minerals in vertebrate bones recrystallize from metastable biogenic forms to thermodynamically more stable inorganic apatite minerals while incorporating REEs from their environment. More than ~95% of the REE in fossil bones are diagenetically incorporated postmortem and bones in different environments have different and distinct REE signatures, generally viewed to be controlled by sedimentological and taphonomic processes. The REE pattern in fossils is generally stable and the normalized concentration patterns provide unique “fingerprints” or signatures that have been used for various geological and paleontological investigations. The discovery of embryos and their adults at the same site, a previously unrecorded occurrence in the fossil record, allowed us to compare for the first time the relationship between REE concentrations in the same taxon at widely differing ontogenetic stages. Here we compare REE patterns in bones from two distinct sites in Yunnan, China, both preserving embryonic and adult bones of Early Jurassic sauropodomorph dinosaurs. These dinosaurs are closely related to each other and close in geological age, and their bones show very similar REE patterns. However, the embryonic bones have significantly lower levels of total REEs when compared to their adult counterparts. We attribute the tenfold difference to the level of ossification of the bones and the dramatically lower concentration of apatites in the embryonic than in the adult bones. We conclude that the ontogenetic stage of fossil materials can have a significant impact on REE concentrations, and discuss the impact of these results on future work.